PSYCHOLOGICAL EMPOWERMENT AND EMPLOYEE ENGAGEMENT IN MILLENNIAL GENERATION EMPLOYEES - Krisnova Nastasia; Rika Wahyuni; Selvi Zola Fenia; Hadi Irfani; Sari Rahmadani (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
objective – The aim of this research is to determine the mediating role of job satisfaction in the effect of psychological empowerment on employee engagement. Design/Methodology/Approach - The population of this study is millennial generation employees at BUMN companies in Padang City. A sample of 67 respondents was taken through cluster random sampling technique, 15 companies were selected as research locations. The research instrument was a questionnaire in the form of a Likert scale. Testing the data through quantitative data analysis techniques structural equation models namely Structural Equation Modeling - PLS-based SEM. Findings – Research findings from SmartPLS v. data processing results. 3 shows that all the proposed hypotheses are proven to be supported. Psychological empowerment has a positive and significant (significant) effect on job satisfaction, psychological empowerment has a positive and significant (significant) effect on employee engagement, job satisfaction has a positive and significant (significant) effect on employee engagement, job satisfaction has no role in mediating psychological influences empowerment on employee engagement. Research limitations – This research is limited to the employee engagement variable and the research data was taken from 1 BUMN company in Padang City. Thus, the results of the study cannot be concluded in general. Originality – The research focus is on the effect of psychological empowerment on employee engagement and looking at the mediating role of job satisfaction variables.